Nurturing education quality through impactful research: Insights from Bahir Dar Journal of Education July 2023 issue - Mulugeta Yayeh Worku (College of education, Bahir Dar University, 2023)
Welcome to the third issue of Bahir Dar Journal of Education for the year 2023. In this issue, we publish eight manuscripts authored by a total of seventeen scholars. They cover a variety of topics pertaining to education. From the challenges faced in implementing 21st-century skills, authentic learning, and time management to parents' concerns over television viewing's impacts on children's education and well-being, the papers attempt to address various educational challenges. Each manuscript brings unique insights and recommendations that collectively contribute to the ongoing quest for quality education.